Progress of State of Health Evaluation Methods for Lithium-ion power Battery. Issue 3 (December 2018) - Liu, Ping; Zhang, Wenhua; Tan, Qingfeng; Liu, Xiaolei; Wu, Fayuan
Abstract: With the wide application of lithium ion battery in the energy storage system, Much attention had been paid to the state of health (SOH) evaluation research. In this paper, the research advance of SOH evaluation methods for lithium-ion battery was reviewed. Several main SOH evaluation methods, including defining method, internal resistance method, AC impedance, voltage curve method, model method and some new methods, were discussed in detail. And finally the research direction of further progress in this area was proposed.